PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM (Survei pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2017) - Krida Siti Hamidah; Untung Sriwidodo; Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2020)
The purpose of this research are to find out the influences of current ratio, debt to equity ratio, and rupiah exchange rate on the stock prices of food and baverage companies in Indonesia Exchange period 2015 - 2017. This research used population of 19 food and baverage compenies in Indonesia Exchange period 2015 - 2017. Samples in this research are 14 companies with samples technique is purposive sampling. Data analysis techniques used in this research are classical assumption test, mutiple linear analysys, and hypotesis test. The result show that partially rupiah exchange rate has significant effect on the stock price, while current ratio and debt to equity ratio has no influence on the stock price. Simultaneously current ratio, debt to equity ratio and rupiah exchange rate has significant effect on the stock price.